2022
DOI: 10.1124/molpharm.121.000420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sarcomere Activators and Inhibitors Targeting Myosin Cross-Bridges on Ca2+-Activation of Mature and Immature Mouse Cardiac Myofilaments

Abstract: We tested the hypothesis that isoform shifts in sarcomeres of the immature heart modify the effect of cardiac myosin-directed sarcomere inhibitors and activators. Omecamtiv mecarbil (OM) activates tension and is in clinical trials for the treatment of adult acute and chronic heart failure.Mavacamten (Mava) inhibits tension and is in clinical trials to relieve hyper-contractility and outflow obstruction in advanced genetic hypertrophic cardiomyopathy (HCM) linked commonly to mutations in sarcomeric proteins. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…We reported in vitro studies that demonstrated that OM increased the Ca 2+ sensitivity of Tm-E54K myofilaments [109]. Although also reported by others, the effect of OM to increase sarcomere Ca 2+ sensitivity and modify cooperative activation is not generally discussed in considerations of its mechanism of action [110,111]. Kieu et al [112] reported that at physiological temperatures, there is a prominent effect of OM in increasing skinned fiber sub-maximal tensions in the force-Ca 2+ relation with no effect on maximum tension.…”
Section: Myosin Heavy Chain As a Drug Targetmentioning
confidence: 89%
“…We reported in vitro studies that demonstrated that OM increased the Ca 2+ sensitivity of Tm-E54K myofilaments [109]. Although also reported by others, the effect of OM to increase sarcomere Ca 2+ sensitivity and modify cooperative activation is not generally discussed in considerations of its mechanism of action [110,111]. Kieu et al [112] reported that at physiological temperatures, there is a prominent effect of OM in increasing skinned fiber sub-maximal tensions in the force-Ca 2+ relation with no effect on maximum tension.…”
Section: Myosin Heavy Chain As a Drug Targetmentioning
confidence: 89%
“…We reported in vitro studies that demonstrated that OM increased the Ca-sensitivity of Tm-E54K myofilaments [105]. Although we and others had previously reported an effect of OM to increase sarcomere Ca-sensitivity [106,107], and modify cooperative activation, this effect is not generally discussed in considering the mechanism of action. Kieu et al [108] reported that at physiological temperatures there is a prominent effect of OM in increasing skinned fiber sub-maximal tensions in the force-Ca relation with no effect on maximum tension.…”
Section: Myosin Heavy Chain As a Drug Targetmentioning
confidence: 96%
“…It is a serious disease often seen in cardiology clinics. When AMI occurs in heart failure, the main pathophysiological event is cardiac remodeling which leads to apoptosis and hypertrophy of cardiac cells, as well as myocardial fibrosis and inflammatory response [2]. The use of anti-inflammatory drugs results in significant inhibition of AMI, thereby protecting myocardial function, and preventing extracellular matrix accumulation.…”
Section: Introductionmentioning
confidence: 99%